2022
DOI: 10.1002/lpor.202100726
|View full text |Cite
|
Sign up to set email alerts
|

Parametric Nonlinear Optics with Layered Materials and Related Heterostructures

Abstract: Nonlinear optics is of crucial importance in several fields of science and technology with applications in frequency conversion, entangled‐photon generation, self‐referencing of frequency combs, crystal characterization, sensing, and ultra‐short light pulse generation and characterization. In recent years, layered materials and related heterostructures have attracted huge attention in this field, due to their huge nonlinear optical susceptibilities, their ease of integration on photonic platforms, and their 2D… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 298 publications
(575 reference statements)
1
19
0
Order By: Relevance
“…Nonlinear optics with atomically thin and layered materials has proven to be a powerful spectroscopic approach to study the physics of excitons confined at the ultimate thickness limit, as well as a fruitful playground to test novel ultrafast and ultrathin optical devices. [ 1 ] Parametric harmonic generation has been used to probe interlayer excitons in homo‐ [ 2 ] and hetero‐bilayers, [ 3 ] and to detect quantum interference pathways and strong coupling in monolayer transition metal dichalcogenides (TMDs). [ 4 ] Furthermore, nonlinear optical properties of layered materials are adding a rapidly growing number of applications in optics, which already include electrical [ 5 ] and all‐optical [ 6 ] ultrafast and broadband frequency converters, miniaturized logic gates, [ 7,8 ] photonic integrated gas sensors, [ 9 ] nonlinear holograms, [ 10 ] and ultrathin quantum sources based on spontaneous parametric down conversion (SPDC).…”
Section: Introductionmentioning
confidence: 99%
“…Nonlinear optics with atomically thin and layered materials has proven to be a powerful spectroscopic approach to study the physics of excitons confined at the ultimate thickness limit, as well as a fruitful playground to test novel ultrafast and ultrathin optical devices. [ 1 ] Parametric harmonic generation has been used to probe interlayer excitons in homo‐ [ 2 ] and hetero‐bilayers, [ 3 ] and to detect quantum interference pathways and strong coupling in monolayer transition metal dichalcogenides (TMDs). [ 4 ] Furthermore, nonlinear optical properties of layered materials are adding a rapidly growing number of applications in optics, which already include electrical [ 5 ] and all‐optical [ 6 ] ultrafast and broadband frequency converters, miniaturized logic gates, [ 7,8 ] photonic integrated gas sensors, [ 9 ] nonlinear holograms, [ 10 ] and ultrathin quantum sources based on spontaneous parametric down conversion (SPDC).…”
Section: Introductionmentioning
confidence: 99%
“…[ 45,46,51 ] In this regard, semiconducting MX 2 TMDs can provide many chances with strong excitonic effects manifesting at broad wavelengths. [ 45,46,51,52 ] For instance, our findings showed that monolayer and spiral MoSe 2 would be an excellent candidate for an efficient ultrathin nonlinear device working at the optical communication bands, O‐ to L‐band, 1260–1625 nm. As can be seen in Figure 6b, the values of χ (2) surpassed a few tens of pm V −1 in the range of 600–840 nm, including the whole of half of O‐ to L‐band wavelengths.…”
Section: Resultsmentioning
confidence: 89%
“…First, we schematically reiterate the sensing mechanism in Figure 3a: the out‐of‐plane π bonds in graphene are highly sensitive to polar gases. [ 41,42 ] When adsorbed on graphene, gases such as NO 2 and H 2 O act as electron acceptors, whereas gases such as NH 3 and CO 2 act as electron donors. [ 36,43 ] Thus, starting from our originally p‐doped graphene on silica ( E F ≈ 0.2 eV, as obtained from Raman spectroscopy shown in Note S2, Supporting Information), [ 45 ] NO 2 and H 2 O adsorption will increase the | E F |, while vice versa the NH 3 and CO 2 adsorption will decrease the | E F |.…”
Section: Resultsmentioning
confidence: 99%